How Blockchain Affects the Technological Strategy of the Financial Industry: An Analysis Based on Knowledge Discovery in Text - Fernandes, Marcelo Vighi; Verschoore, Jorge Renato (Future Studies Research Journal: Trends and Strategies, 2020)
Purpose – The main objective of this article is to investigate how blockchain is affecting the technological strategy of the financial industry. Theoretical framework – Our theoretical framework is structured based on four approaches: Blockchain; Blockchain Advantages; Technology Strategy; Blockchain Technology Strategy. Design/methodology/approach – We conducted an exploratory study using knowledge discovery in texts (KDT), with the support of text mining tools. We collected and analyzed contents of a set of news published on the Web about Blockchain. A total of 2,605 blockchain web news items were extracted from the business media worldwide, such as Forbes, Fortune, Financial Post and Business World. We explored the text dataset using sentiment analysis, opinion mining, text association analysis, and correspondence analysis. Findings – The results showed that blockchain technology has the potential to affect the transactions through a common platform. Additionally, the results demonstrated the advantages of blockchain technology for cross-border payment systems. Research, Practical & Social implications – We elaborate four theoretical propositions that may guide research and help practitioners to identify challenges and opportunities for blockchain technology. Originality/value – Our study revealed how blockchain has been affecting the technology strategy of the financial industry and highlighted two starting trajectories: the establishment of private blockchain and its application in the cross-border payment services.